The genre-forming characteristics of the english-language microblog twitter - Goncharova Elena A. (Актуальные проблемы филологии и педагогической лингвистики, 2019)
The article is devoted to the genre-forming characteristics of the English-language microblog Twitter, in particular, the communicative goal of media communications is analyzed as informative, fatal, entertaining, self-presentation, evaluative, educational, marketing or economic, political. Participants of communication are considered (addreser / addressee) who, being in an equal communicative position, carry out effective potential speech infuence on each other. The event content of tweets, which by their nature are eventful, emotional, communicative, synthetic messages, is investigated. The author convincingly argues that Twitter, on the one hand, is a virtual space with technical characteristics inherent only to it, but on the other hand, the microblog is a unique communicative genre that defnes certain rules of speech behavior that communicants have to follow. The article attempts to highlight the linguistic genre-forming features of the design of tweets that determine the choice of lexical, stylistic, syntactic, graphic and other means. When creating a model of the speech genre of Twitter, the author correlates it with the above parameters, including in the description information about extra-linguistic factors that affect the language embodiment of this type of communication. It has been suggested that Twitter is a converged Internet genre that emerged from the advent of Web 2.0 technology. Being a hybrid genre, this communicative phenomenon is interesting for linguistic analysis due to a number of characteristic communicative features, namely: focus on the recipient, the ability to instantly respond to media messages, freedom of expression.